Potensi Pasar Tradisional dalam Meningkatkan Kesejahteraan Ekonomi Berdasarkan Pendekatan Ekonomi Islam - Aysah, Siti (PT. Anagata Sembagi Education, 2024)
This type of research is categorized as qualitative category by using a sociological approach. Researchers are involved in interactions with the environment in accordance with social units such as individuals, groups, institution, or society. The data collection methods used include literature survey, observation, and interviews. Data management and analysis process through three stages, namely data collection, data reduction, data presentation, and conclusion drawing. the final stage is conclusion drawing. The results showed that Cekkeng traditional market has the potential to improve the traders' economy. The potential of Cekkeng market market, among others, are more affordable prices compared to other traditional markets, a variety of product market, a wide variety of products, and a strategic location and time. strategic location and time. In addition, supporting factors that play an important role are attention from the local government, including price monitoring, prevention of fraud, and handling of damaged goods and demoralizing actions.